(untitled) (Journal of Engineering, 2023)
Construction projects are characterized as projects with multi phases and activities, complex, unique, and have many different parties and stakeholders. Risks could appear at one or more of the construction project stages and may affect the achievement of project objectives. Therefore, one of the key elements in the planning phase of any project is the risk management process (RMP). This study attempts to understand the terminology of risk in general, risk management, and response to risk in particular. This study is mainly a review of thirty-eight studies that have been published between 1997 and 2020 that demonstrate the importance of the crucial phase of risk response from the risk management process and its impact on the project objectives, as well as the tools and methodologies that project managers and decision-makers could use to handle the risks to reduce the negative effects of risks on the success of the construction projects. This study concludes that risk response should be considered an essential activity to complete the RMP, which will lead to minimizing the losses due to risks, maximizing the benefits due to opportunities, and achieving the objectives of projects.